Comparison Between Esketamine and Alfentanil for Hysteroscopy: A Prospective, Double-Blind, Randomized Controlled Trial - Weng M; Wang D; Zhong J; Qian M; Zhang K; Jin Y (Drug Design, Development and Therapy, 2024)
Mengcao Weng,1,* Dongdong Wang,2,* Jia Zhong,2 Minyue Qian,1 Kai Zhang,2 Yue Jin1 1Department of Anesthesiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Anesthesiology, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yue Jin, Department of Anesthesiology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, 3333 Binsheng Rd, Hangzhou, Zhejiang, 310052, People’s Republic of China, Tel +8613456912018, Email yue_jin@zju.edu.cn Kai Zhang, Department of Anesthesiology, the First Affiliated Hospital, Zhejiang University School of Medicine, Wenyixi Road 1367, Hangzhou, 311121, People’s Republic of China, Tel +8615858281107, Email comezk@zju.edu.cnPurpose: This study aimed to establish the 95% effective dose (ED95) of esketamine in combination with propofol for hysteroscopy and then to evaluate its efficacy and safety profile.Patients and Methods: This prospective, double-blind, randomized controlled trial consisted of two cohorts. In cohort 1, 45 women aged 18– 65 years undergoing hysteroscopy were randomly assigned to either group E (esketamine + propofol) or group A (alfentanil + propofol). Dixon’s up-and-down method was used to determine the ED95 of esketamine and alfentanil. In cohort 2, 86 patients were randomized to group E and group A, with the calculated ED95 dose of the study drugs used for induction. The success rate of anesthesia using the ED95% dose, along with parameters related to anesthesia induction, recovery, and adverse events were also recorded.Results: The ED95 of esketamine was 0.254 mg/kg (95% CI: 0.214– 1.004), while that of alfentanil was 9.121 μg/kg (95% CI: 8.479– 13.364). The anesthesia success rate was 93.0% in group E and 95.2% in group A (p = 0.664). After resuscitation, both groups achieved a 100% success rate. The induction time was significantly shorter in group E (60.0 [55.0– 70.0] s) compared to group A (67.0 [61.0– 79.3] s) (p = 0.006). Group E had lower rates of respiratory depression (p < 0.001), hypoxia (p = 0.006), minimum perioperative SpO2 (p = 0.010), and hypotension (p = 0.001). Esketamine had less effect on respiratory rate, heart rate, mean blood pressure, and end-tidal carbon dioxide compared to alfentanil (all p < 0.001). There were no significant differences in postoperative pain between the two groups.Conclusion: This study determined the ED 95 dose of esketamine for intravenous general anesthesia during hysteroscopy. Esketamine showed less respiratory and hemodynamic depression, as well as fewer adverse effects compared to alfentanil. Esketamine is an ideal anesthetic agent compared to alfentanil for hysteroscopic anesthesia.Trial Registration: www.chictr.org.cn, (ChiCTR2300077283); registered November 3, 2023.Keywords: esketamine, 95% effective dose, hysteroscopy, propofol